Abuse liability assessment of the JUUL system in four flavors relative to combustible cigarette, nicotine gum and a comparator electronic nicotine delivery system among adult smokers. (1st December 2020) - Goldenson, Nicholas I.; Buchhalter, August R.; Augustson, Erik M.; Rubinstein, Mark L.; Henningfield, Jack E.
Highlights: Abuse liability of the JUUL System (JS) 5.0 % (59 mg/mL) in 4 flavors was assessed. High- (combustible cigarette) and low-abuse liability (nicotine gum) comparators. Nicotine delivery and satisfying effects of JS were less than cigarettes. Nicotine delivery and satisfying effects of JS were greater than nicotine gum. Abuse liability of JS is likely lower than cigarettes and higher than nicotine gum. Abstract: Background: The abuse liability of the JUUL System (JS) in four flavors were evaluated compared to combustible cigarettes, nicotine gum, and a comparator electronic nicotine delivery system (ENDS) with pharmacokinetics (PK) and subjective effects. Methods: Adult smokers (N = 66; 50.0 % female; mean age = 41.1; 63.6 % white) completed a 7-arm within-subjects cross-over product-use study while confined to a clinical laboratory. Participants used JS in four flavors (Virginia Tobacco, Mango, Mint, Creme, [5.0 % nicotine; 59 mg/mL]), their usual brand (UB) cigarette, a comparator ENDS (VUSE Solo; 4.8 % nicotine, tobacco-flavor), and mint nicotine gum (4 mg) under controlled use conditions. After each product use, nicotine PK and subjective effects were assessed. Results: Maximum plasma nicotine levels (Cmax-BL ), rate of plasma nicotine rise, overall nicotine exposure (AUC0−60-BL ), and subjective liking and satisfaction of JS were significantly lower than UB cigarettes. These parameters were generally greater for JS than nicotine gum; the comparator ENDS was somewhat lower but within the range of JS. Nicotine PK did not differ among the Mint, Mango, and Virginia Tobacco JS flavors. Mint and Mango were rated as more satisfying than Virginia Tobacco and Creme. Conclusions: Controlled use of JS among adult smokers resulted in nicotine delivery, product liking, and satisfaction that were less than that of combustible cigarettes but generally greater than nicotine gum. These results support the conclusion that JS has lower abuse liability than combustible cigarettes, higher abuse liability than nicotine gum, and may provide sufficient nicotine delivery and satisfying effects to support substitution for combustible cigarettes among adult smokers.